Effect of Room Service on Patient’s Macronutrient Consumption Level - Arfiani, Eva Putri; Yati Soenarto; Susetyowati (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2023)
Food service in hospital is aimed at providing high-quality meals and ensuring nutrition intake for patients. However, this aspect of healthcare faces numerous challenges, including high levels of food waste and patient dissatisfaction, often attributed to conventional food delivery practices in hospitals. The consumption of energy and macronutrients, including carbohydrate, protein, and fat, contribute greatly for hospitalized patients. Therefore, this study tried to implement a room service-like method in the food service system. This research was conducted in Class 1 and 2 of the inpatient wards of “Waled” Public Hospital, using a static pre-experimental design with two groups. Each group consisted of 38 patients selected from quota sampling. The control group followed the conventional food service method, while treatment group was given a room service approach. The treatment group was provided with a list of three menu options for each of the nine mealtimes, allowing them to choose their preferred food by sending a short message at the designated meal hour. Ordering times were specified as follows: 05:15 to 07:00 for breakfast, 10:00 to 12:00 for lunch, and 15:00 to 17:00 for dinner. Foods were prepared within 45 minutes after the order was placed. T-test analysis showed a distinct trend in the levels of energy, carbohydrates, proteins, and fats consumption between the control and treatment groups. The correlation between group variables and the level of energy consumption reached 15%, while the correlation between group variables and the level of protein consumption was 14%.